An Optimal Design of Multiple Antenna Positions on Mobile Devices Based on Mutual Coupling Analysis - Peerapong Uthansakul; Danai Assanuk; Monthippa Uthansakul (International Journal of Antennas and Propagation)
The topic of practical implementation of multiple antenna systems for mobile communications has recently gained a lot of attention. Due to the area constraint on a mobile device, the problem of how to design such a system in order to achieve the best benefit is still a huge challenge. In this paper, genetic algorithm (GA) is used to find the optimal antenna positions on a mobile device. Two cases of 3×3 and 4×4 MIMO systems are undertaken. The effect of mutual coupling based on Z-parameter is the main factor to determine the MIMO capacity concerning the objective function of GA search. The results confirm the success of the proposed method to design MIMO antenna positions on a mobile device. Moreover, this paper introduces the method to design the antenna positions for the condition of nondeterministic channel. The concern of channel variation has been included in the process of finding optimal MIMO antenna positions. The results suggest that the averaging position from all GA solutions according to all channel conditions provides the most acceptable benefit.